Seiberg-Witten Like Equations on Pseudo-Riemannian Spinc Manifolds with G2(2)∗ Structure - Nülifer Özdemir; Nedim Deǧirmenci (Advances in Mathematical Physics)
We consider 7-dimensional pseudo-Riemannian spinc manifolds with structure group G2(2)∗. On such manifolds, the space of 2-forms splits orthogonally into components Λ2M=Λ72⊕Λ142. We define self-duality of a 2-form by considering the part Λ72 as the bundle of self-dual 2-forms. We express the spinor bundle and the Dirac operator and write down Seiberg-Witten like equations on such manifolds. Finally we get explicit forms of these equations on R4,3 and give some solutions.